Os bondes de pista: a briga como possibilidade de lazer para grupos de torcedores de futebol no Brasil - Fábio Henrique França Rezende (2024)
Given the countless possibilities that exist, when related to football, cheering presents itself as an important leisure practice. Thus, the formation of specific fan groups, such as “Bondes de pista”, happens through sociability processes resulting from emotional engagement and/or common elements, such as the fact that they view fights as leisure practices and a lifestyle. Therefore, this study was carried out due to the need to advance discussions and understandings about these fan groups, in order to reflect and debate about “Bondes de pista”, cheering and the clashes related to them. This study has a qualitative, exploratory approach, being divided into a bibliographical review, semi-structured interviews with the leaders of the “Bondes de pista” and field research. As a general objective, I sought to analyze the performance of “Bondes de pista”, through fights and pre-established rules of conduct for confrontations. As specific objectives, I sought to understand the norms, internal dynamics, aspects of sociability and the meaning of fights for these fan groups. They show themselves as a fan and cultural manifestation that has been gaining prominence whether inside or outside the Brazilian stands. Respect for the rules of conduct for clashes enabled the resurgence of a fan consciousness that is nurtured in physical clashes and the dispute over symbolic territories. The present study allowed the perception of fights based on the idea of play and not extermination. That said, I characterize these groups as complex subjects who go beyond the logic of violent people, who show themselves as multifaceted characters and who use the protagonism of fight fans to direct them towards a counter-hegemonic perspective in terms of using disputes as conscious, voluntary, playful acts that provide opportunities for the creation of bonds of friendship, respect and unity between its members.